EVALUATION OF SIDEWALK BASED ON THE INDONESIAN GUIDELINE FOR TECHNICAL PLANNING OF PEDESTRIAN FACILITIES - Supriyana Supriyana Supriyana; Rachmat Mudiyono; Sumirin Sumirin (Pondasi, 2022)
Sidewalks are pedestrian paths generally parallel to road and higher than the pavement surface to ensure the safety of pedestrians. Sidewalk is important for pedestrians; thus, it has to meet the standards of technical requirement. This study aimed to evaluate condition of sidewalk in Kudus City, Indonesia to find out whether the existing sidewalks had complied with the technical requirement as stipulated in the Indonesian guideline for technical planning of pedestrian facilities. This was a descriptive quantitative study involving sidewalks as the sample. Data were collected through survey and analyzed quantitatively. Despite having several issues around design of the construction, the existing sidewalk in Kudus City, Indonesia had been in accordance with the provision as prescribed in the Indonesian guideline for technical planning of pedestrian facilities. Finding of the study suggested that sidewalks need for further improvement for the convenience of pedestrians, especially signposts, sidewalk accessories, direction and other relevant properties.Keywords: Descriptive qualitative study, Indonesian standard of public facilities development, pedestrians, sidewalks